2017
DOI: 10.7324/ijcrr.2017.9144
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Gender Differentials of Metabolic Syndrome Among College Students of Kolkata, West Bengal, India

Abstract: Aim:The study aims to determine the prevalence of metabolic syndrome (MS) and assess gender differences among college students of Kolkata, West Bengal, India using International Diabetes Federation (IDF) criteria. Materials and Methods:Design: A cross sectional study was conducted among 397 college going students comprising of 235 females and 162 males aged 18 to 24 yrs from August 2011 to December, 2013. Measurements: Anthropometric measurements were performed by standardized techniques, blood pressure (BP) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(50 reference statements)
0
0
0
Order By: Relevance
“…Globally, our frequency exhibited a higher prevalence compared to numerous other frequencies. A systematic review conducted in the United States and South America revealed that the prevalence of MetS ranged from 0% to 19.2%, as determined by the NCEP-ATPIII-20 criteria [31]. This prevalence surpassed the frequencies reported in previous studies conducted among university students in various countries, including Kenya, the United States, India, Brazil, and Korea [32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 86%
“…Globally, our frequency exhibited a higher prevalence compared to numerous other frequencies. A systematic review conducted in the United States and South America revealed that the prevalence of MetS ranged from 0% to 19.2%, as determined by the NCEP-ATPIII-20 criteria [31]. This prevalence surpassed the frequencies reported in previous studies conducted among university students in various countries, including Kenya, the United States, India, Brazil, and Korea [32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 86%